Social Entrepreneurship Ecosystems: A Systematic Literature Review - Bozhikin, Ivan (Research Papers, 2020)
Social entrepreneurship has gained popularity over the past two decades. This has led to a significant increase in scientific literature in this area, while the public sector increasingly recognizes social entrepreneurship as a key tool for overcoming social problems in society and strengthening sustainable development. The purpose of this article is to explore ecosystems for social entrepreneurship presented in the scientific literature. To achieve this research goal, a literary review of the 20 most cited articles exploring ecosystems for social entrepreneurship is made. A descriptive analysis of the selected articles has been carried out. Types of social entrepreneurship ecosystems and the social problems solved with them are presented. Key players in social entrepreneurship ecosystems and important factors contributing to the development of social entrepreneurship ecosystems are pointed out.
Keywords: Ecosystems; Economic agents; Factors; Social entrepreneurship